Improving business incubator service performance in China: the role of networking resources and capabilities - Lin, D; Wood, LC; Lu, Q (Taylor & Francis, 2012)
This research analyses the relationships between resources and capabilities in Chinese business incubators to determine the relative importance in enhancing the service performance of incubators. A mixed-method design is used consisting of an in-depth case study and structural equation modelling based on survey data. Incubator managers are advised to invest in infrastructural and external resources and networking capabilities, which are positively correlated with performance. We find that resources relating to government policy, such as funding, may have a negative impact on incubator performance while other integrated service capabilities have little correlation with improved performance.
Keywords: Business incubator; Service performance; Resource-based view